The engine immobilizer: A non-starter for car thieves - Jan C. van Ours; Ben Vollaard (Center for Economic Studies and ifo Institute (CESifo), 2013)
We provide evidence for a beneficial welfare impact of a crime policy that is targeted at strengthening victim precaution. Regulation made application of the electronic engine immobilizer, a simple and low-cost anti-theft device, mandatory for all new cars sold within the European Union as of 1998. We exploit the regulation as source of exogenous variation in use of the device by year of manufacture of cars. Based on detailed data at the level of car models, we find that uniform application of the security device reduced the probability of car theft by an estimated 50 percent on average in the Netherlands during 1995-2008, accounting for both the protective effect on cars with the device and the displacement effect on cars without the device. The costs per prevented theft equal some 1,500 Euro; a fraction of the social benefits of a prevented car theft.
Keywords: H11; H23; K42; 330; car theft; government regulation; crime; victim precaution; Kraftfahrzeug; Sicherheitstechnik; Prävention; Regulierung; Wirkungsanalyse; Kriminalität; Niederlande